New Publications (Journal of Political Economy, 1908)
The Journal seeks to cover, in its monthly bibliography, all current literature of economic interest in the following fields: I. Books published in the English, French, German, and Italian languages. II. The government publications of the United States and of Great Britain. III. Periodical references of four or more pages appearing in the periodicals listed below. Periodicals devoting an entire number to a single discussion are listed under books.